Biosignal-Based Attention Monitoring to Support Nuclear Operator Safety-Relevant Tasks - Kim, Jung Hwan; Kim, Chul Min; Jung, Eun-Soo; Yim, Man-Sung (Frontiers in Computational Neuroscience, 2020)
In the main control room (MCR) of a nuclear power plant (NPP) the quality of an operator’s performance can depend on their level of attention to the task. Insufficient operator attentions accounted for more than 26% of the total causes of human errors and is the highest category for errors. Therefore, it is necessary to check whether operators are sufficiently attentive either as supervisors or peers during reactor operation. Recently, digital control technologies are introduced to the operating environment of an NPP MCR. These upgrades are expected to enhance plant and operator performance. At the same time, because personal computers are used in the advanced MCR, the operators perform more cognitive works than physical work. However, operators may not consciously check fellow operators’ attention in this environment indicating potentially higher importance of the role of operator attention. Therefore, remote measurement of an operator’s attention in real-time would be a useful tool providing feedback to his/her supervisor. The objective of this study is to investigate the development of quantitative indicators that can identify an operator’s attention, to diagnose or detect a lack of operator attention thus preventing potential human errors at advanced MCRs. To establish a robust baseline of an operator’s attention, this study used two of the widely used biosignals, electroencephalography (EEG) and eye movements. We designed an experiment to collect EEG and eye movements of the subjects who were monitoring and diagnosing nuclear operator safety-relevant tasks. There was a statistically significant difference between biosignals with and without appropriate attention. Furthermore, an average classification accuracy of about 90% was obtained by the k-nearest neighbors (kNN) and support vector machine (SVM) classifiers with a few EEG and eye movements features. Potential applications of EEG and eye movement measures in monitoring and diagnosis tasks in NPP MCR are also discussed.